OPTIMIZATION OF MORALS MATERIAL IN PAI LEARNING AT JUNIOR HIGH SCHOOL LEVEL: SOCIAL COGNITIVE THEORY PERSPECTIVE - Hikayat, Bunga Anisa; Anwar, Saepul; Muflihah, Nisa; Febriani, Rizka (Al-Qalam, 2025)
Coaching moral students in Indonesia has become the biggest challenge, as there is evidence from various government and institutional data showing a high number of bullying incidents, especially at the elementary level, including School Intermediate First (Junior High School). This article discusses the optimization of PAI element material morals that also play a role in building moral students. In particular, research was conducted to study various components of PAI element material morals based on Albert Bandura's social cognitive theory. This method is qualitative descriptive, analyzing data sources in the PAI Teacher and Student Book, as well as supporting data from related literature. The results showed a mismatch between the teaching materials and the achievement learning that has been determined, specifically Mark Sincere and Loving Darling, which are not listed in the textbook. Based on perspective theory and social cognitive research, this highlights the importance of coaching morals and their application through three aspects: personal, behavioral, and environmental. Implications study. This is an important analysis, evaluation, and development of PAI teaching materials to meet the needs of students and the national education system.